Seismic cone penetration testing in the near offshore of the MacKenzie Delta - Campanella, R. G.; Robertson, P. K.; Gillespie, D.; Laing, N.; Kurfurst, P J (Canadian Geotechnical Journal, 1987)
A study was performed in the shallow waters of the MacKenzie Delta area near Tuktoyaktuk, N.W.T., Canada, to evaluate equipment, test procedures, and techniques using a seismic cone penetrometer and operating on the landfast ice in winter. Seismic cone penetration testing was performed to determine the compressional and shear wave velocities of the subsurface sediments using a downhole technique. Several seismic sources and receivers were tested to evaluate their effectiveness. Typical results are presented and briefly discussed. Key words: downhole, seismic, P-wave, S-wave, velocity, in situ, measurement, shallow offshore, cone penetration test.